Playing Purposefully with Students in Courses – a Concept, an Implementation, and an Evaluation of a University Module - Moser, Gabriela (Central European Journal of Educational Research, 2025)
Playing as a method of learning is predominantly applied in preschool and primary education. However, in the context of higher education, the method of playing is only sporadically used. The novelty of this topic lies in its application at the tertiary level, particularly in teacher education, where the aim is for students to plan and support learning processes for pupils from deep structures. This study investigates how playful learning methodologies can be effectively integrated into higher education and examines the impact on student attitudes and teaching practices. The module ’Playful Learning in Primary Education’ was evaluated during the autumn semester of 2023 at the Institute for Primary Education of the PH FHNW in Switzerland. Initially, the topic of play is defined from multiple theoretical perspectives. The module description outlines the research questions addressed in the study. A central component of the evaluation is the students’ certificates of achievement, which were analyzed using qualitative content analysis. The results highlight the attitudes toward playful methodology that students had at the beginning of the module and the attitudes and experiences they acquired by the end of the module. The evaluation results are presented in summative fashion in tables and interpreted in the discussion. The article aims to motivate university teachers to offer playful learning methods in higher education and to experience the positive impacts of this methodology with the students. The results clearly show that this methodology can lead to changes in teaching practice.